LEUKOTACTIC FACTORS ELABORATED BY VIRUS-INFECTED TISSUES - Ward, Peter A. (The Rockefeller University Press, 1972)
Infection of chick embryos wih either Newcastle disease virus or mumps virus and infection of BGM cell cultures with mumps virus result in the elaboration of chemotactic activity for neutrophils and macrophages. These factors cannot be found in lysates of uninfected cells. They do not appear to be associated with the viral particles per se, but rather are present in virus-free supernates from infected fluids. Ultracentrifugal studies of the neutrophil chemotactic activity in allantoic fluid of embryos infected with the two different viruses indicate a similar biphasic distribution of activity, while fluid from the mammalian cell cultures shows a single zone of leukotactic activity, further suggesting that the infected cell, rather than the virus, is responsible for the leukotactic activity. Virus-infected cells also release a substance(s) which is itself not leukotactic but which can interact with human C3 or C5 to generate such activity. This leukotactic factor-generating substance is similar to that reported in another virus-infected cell system. It is postulated that the leukotactic factors elaborated as a result of virus infection of cells may play a protective role in vivo.